2016
DOI: 10.4103/0973-1075.179605
|View full text |Cite
|
Sign up to set email alerts
|

Profile of malignant spinal cord compression: One year study at regional cancer center

Abstract: Background and Objectives:Malignant spinal cord compression is an oncologic emergency, unless diagnosed early and treated appropriately, can lead to permanent neurological impairment and compromised quality of life of patients. We analyzed the epidemiology and the effect of common interventions on the outcome in these patients.Patients and Methods:We conducted a prospective study of 77 patients in the year 2014 and recorded relevant patient and disease characteristics. All patients received corticosteroids. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Only 42% of patients have paraspinal mass compressing the spinal cord, 25% of the studied populations have visceral mets at time of diagnosis. In the study done by Malik Tariq Rasool, Kaneez Fatima et al ,the type of vertebrae that had been affected in studied population was dorsal (72%), lumber (27.5%),cervical( 8%) (Rasool, Fatima et al 2016).…”
Section: 014mentioning
confidence: 90%
See 4 more Smart Citations
“…Only 42% of patients have paraspinal mass compressing the spinal cord, 25% of the studied populations have visceral mets at time of diagnosis. In the study done by Malik Tariq Rasool, Kaneez Fatima et al ,the type of vertebrae that had been affected in studied population was dorsal (72%), lumber (27.5%),cervical( 8%) (Rasool, Fatima et al 2016).…”
Section: 014mentioning
confidence: 90%
“…Malik Tariq Rasool, Kaneez Fatima et al found in their study that15.5 % of MSCC cases were caused by breast cancer, 12.9 % caused by myeloma, 11.6% caused by lung cancer, 10.3% caused by prostate cancer, 49% caused by others (Rasool, Fatima et al 2016). While Bach, Larsen et al stated that 19 % of MSCC cases was caused by prostate cancer, 18% caused by lung cancer 14%caused by breast cancer, 10% caused by renal carcinoma, 4% caused by myeloma and 36% caused by others (Bach, Larsen et al 1990).…”
Section: 014mentioning
confidence: 96%
See 3 more Smart Citations